Lipopolysaccharide-induced immune stress negatively regulates broiler chicken growth via the COX-2-PGE2-EP4 signaling pathway - Liu, Kexin; Zhen, Wenrui; Bai, Dongying; Tan, Haiqiu; He, Xianglong; Li, Yuqian; Liu, Yanhao; Zhang, Yi; Ito, Koichi; Zhang, Bingkun; Ma, Yanbo (Frontiers in Immunology, 2023)
Immune stress in broiler chickens is characterized by the development of persistent pro-inflammatory responses that contribute to degradation of production performance. However, the underlying mechanisms that cause growth inhibition of broilers with immune stress are not well defined. The results in this study revealed that feed intake and body weight gain of broilers were suppressed in response to immune stress induced by lipopolysaccharide (LPS) which is an intrinsic component of the outer membrane of Gram-negative bacteria. Cyclooxygenase-2 (COX-2), a key enzyme that mediates prostaglandin synthesis, was up-regulated through MAPK-NF-κB pathways in activated microglia cells in broilers exposed to LPS. Subsequently, the binding of prostaglandin E2 (PGE2) to the EP4 receptor maintained the activation of microglia and promoted the secretion of cytokines interleukin-1β and interleukin-8, and chemokines CX3CL1 and CCL4. In addition, the expression of appetite suppressor proopiomelanocortin protein was increased and the levels of growth hormone-releasing hormone were reduced in the hypothalamus. These effects resulted in decreased expression of insulin-like growth factor in the serum of stressed broilers. In contrast, inhibition of COX-2 normalized pro-inflammatory cytokine levels and promoted the expression of Neuropeptide Y and growth hormone-releasing hormone in the hypothalamus which improved the growth performance of stressed broilers. Transcriptomic analysis of the hypothalamus of stressed broilers showed that inhibition of COX-2 activity significantly down-regulated the expression of the TLR1B, IRF7, LY96, MAP3K8, CX3CL1, and CCL4 genes in the MAPK-NF-κB signaling pathway. This study provides new evidence that immune stress mediates growth suppression in broilers by activating the COX-2-PGE2-EP4 signaling axis. Moreover, growth inhibition is reversed by inhibiting the activity of COX-2 under stressed conditions. These observations suggest new approaches for promoting the health of broiler chickens reared in intensive conditions.